Analysis of The Final Exam of Odd Semester Grades in Arabic for Fifth Grade Students of MI Kebomlati Tuban / Taḥlīl Bunūd Al Ikhtibār Al Nihā’i Limādati Al Lugah Al Arabiyah Fi Al Madrasah Al Ibtidā’iyah Al Islāmiyah Kebomlati Tūban - Reni Lailina Hidayah; Saadatud Darain; Ahmad Zainun Yusuf; Nur Qomari; Faisal Mahmoud Adam Ibrahim (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2021)
The purpose of this study was to analyze the final grade assessment items in the odd semester of Arabic for fifth-grade students at MI Kebomlati Tuban for the 2020/2021 academic year. This study uses a quantitative approach. The data in this study were obtained through question sheet documents and answers to the fifth-grade students of MI Kebomlati Tuban and were analyzed using formulas according to classical test theory (CTT) by using test validity based on the difference in power, the level of difficulty, and the question fraud. The results of this study are: (1) the results of the different power test show that there are 2 items with very good quality of difference, 19 good items, 7 medium items and 7 other items that do not have different power, even 1 of them has a value negative. So that the 7 items cannot be used; (2) at the level of difficulty, 9 items were found in the "difficult" category, 19 items were in the "medium" category and 14 items were in the "easy" category; (3) As for the quality of distractors in the final assessment questions of this semester, on average, they function well. Keywords: Questions, Question Quality, Evaluation, Arabic Abstrak Tujuan dari penelitian ini adalah untuk menganalisis butir soal penilaian akhir semester ganjil (PAS) mata pelajaran Bahasa Arab siswa kelas V di MI Kebomlati Tuban Tahun Pelajaran 2020/2021. Penelitian ini menggunakan pendekatan kuantitatif. Data dalam penelitian ini diperoleh melalui dokumen lembar soal dan jawaban siswa kelas V MI Kebomlati Tuban, dan dianalisis menggunakan rumus-rumus sesuai teori tes klasik (TTK) dengan menggunakan validitas tes berdasarkan daya beda, tingkat kesukaran, dan pengecoh soal. Adapun hasil dari penelitian ini adalah: (1) hasil uji daya beda menunjukkan terdapat 2 butir soal dengan kualitas daya beda sangat baik, 19 butir soal baik, 7 butir soal sedang dan 7 butir soal lainya tidak memiliki daya beda, bahkan 1 soal diantaranya bernilai negatif. Sehingga 7 butir soal tersebut tidak dapat digunakan; (2) pada tingkat kesukaran ditemukan terdapat 9 butir soal masuk dalam kategori “sukar”, 19 butir soal dengan kategori “sedang” dan 14 butir soal dalam kategori “mudah”; (3) adapun kualitas pengecoh dalam soal penilaian akhir semester ini rata-rata berfungsi dengan baik. Kata kunci: Butir soal, Kualitas soal, Evaluasi, Bahasa Arab